The Impact of Rural Enterprises on Household Savings in China - Qiuxia Zhu (University of Bonn, Center for Development Research (ZEF), 2004)
In view of development policy, capital formation is crucial for economic growth in a country. Since the reform in 1978, China has enjoyed high saving rates. However, in the late 1990s the saving rates rose to such a high level, therefore the economic policy to promote consumption in order to reduce savings was suggested,. This paper attempts explains this paradox of "excessively high saving rates" in relation to the capital accumulation mechanism in rural enterprise (TVEs: Township and Village Enterprises). The determinants of household savings in developing countries is one important topic of the development research. However most studies have ignored investment as one main determinant. In the famous Lewis? model, the savings of farm households for non-farm investment are not considered, because in most cases it is difficult to sort out capitalists from the rural households. The case of the capital formation of TVEs in China offers us an opportunity to test the non farm investment as a saving incentive, because there are no large or small capitalists and landlords available after the agriculture reform in China in 1978. With facts and statistical analyses, this paper has proved that the development of TVEs is an important factor of the high saving rates of rural households since the reform. The way of development of private TVEs and the process of the privatization of the collective showed that owing to the extreme financial discrimination, TVEs underwent an evolution into a financial institution. The demand of TVEs for private credits forced rural households to save and hence function as an informal financial market. The managers have the motivation to save because they want to run a collective TVE or to set up a private TVE. The workers have the motivation to save because they want to get a job or keep their job in TVEs. Using first hand data and statistical analyses, it was plausibly proved that households with manager in TVEs have higher saving rates than non-manager households. It is especially obvious in households with manager in shareholding and shareholding co-operative TVEs. Households with peasant worker in collective TVEs have higher saving rates than others. This implies that collective TVEs used many methods to force their workers to save. – – Unter dem Aspekt der Entwicklungspolitik ist die Kapitalakkumulation von entscheidender Bedeutung für das Wirtschaftswachstum in einem Land. Seit der Reform von 1978 profitierte China von der hohen Sparquote. Ende der 90er Jahren war die Sparquote äußerst hoch, daher wurde eine konsumfördernde Wirtschaftspolitik vorgeschlagen, um diese hohe Sparquote zu verringern. Die vorliegende Arbeit versucht dieses Paradoxon in Zusammenhang mit dem Mechanismus der Kapitalakkumulation in ländlichen Unternehmen (= TVEs: Township and Village Enterprises) zu erklären. Die Bestimmungsfaktoren für das Sparverhalten der Haushalte in den Entwicklungsländern ist ein wichtiger Gegenstand der Entwicklungsforschung. Jedoch wurde die Investition als eine Motivation in den meisten Studien nicht berücksichtigt. Im bekannten Modell von Lewis wurden die Ersparnisse der ländlichen Haushalte ausgeklammert, weil es in vielen Fällen schwierig ist, die Kapitalisten von ländlichen Haushalten zu unterscheiden. Der Fall der Kapitalakkumulation in chinesischen TVEs eröffnet uns die Möglichkeit, die These zu bestätigen, dass die Investition in den nicht-landwirtschaftlichen Sektor als eine wichtige Sparmotivation für ländliche Haushalte zu betrachten ist, da es nach der Agrarreform in China 1978 keine kleinen oder großen Kapitalisten und Landbesitzer gibt. Anhand von Fakten und statistischen Analysen hat diese Arbeit bestätigt, dass die Entwicklung der TVEs entscheidend für die hohe Sparquote der ländlichen Haushalte in China nach der Reform ist. Der Weg der Entwicklung der privaten TVEs und der Prozess der Privatisierung der kollektiven TVEs zeigten, dass die TVEs unter dem Umstand des beschränkten Zugangs zu Krediten zu einer Art Finanzinstitution evolviert. Die Nachfrage nach privaten Krediten führt dazu, dass aufgrund der Funktion der informalen Finanzmärkte die ländlichen Haushalte verstärkt sparen. Die Manager der TVEs haben große Motivation zu sparen, um ein kollektives TVE unter dem Vertrag führen oder um ein privates TVE aufbauen zu können. Die Arbeitnehmer haben große Motivation zu sparen, um einen Arbeitsplatz in TVEs zu erhalten oder zu behalten. Mit Hilfe der Daten aus der Erhebung und der statistischen Analyse wurde klar bestätigt, dass Haushalte mit Managern in TVEs höhere Sparquoten aufweisen als die Haushalte ohne Manager in TVEs. Dies wird besonders deutlich für Haushalte mit Managern in Shareholding und Shareholding kooperative TVEs. Haushalte mit Bauernarbeitern in kollektiven TVEs haben ebenfalls höhere Sparquoten als andere. Dies bedeutet, dass kollektive TVEs mit vielen möglichen Methoden ihre Mitarbeiter zum Sparen zwingen.
Keywords: 330; Sparen; Privater Haushalt; Ländlicher Raum; Ländliche Wirtschaft; Investition; Informeller Finanzsektor; Ländlicher Finanzmarkt; China